Togani - Kong, Chi-yŏng, 1963- (Modern Korean fiction., 2023)
"Atmospheric and fast-paced, this novel of manners set in a provincial South Korean city leads readers through the silent corridors of a school for hearing-impaired children and the city's foggy back streets and murky centers of power to a stirring courtroom climax. Gong Jiyoung's Togani (The Crucible), published in Korean in 2009, is based on a historic case of child sexual abuse at a state-run institution. The novel went on to sell nearly a million copies and, along with a 2011 film adaptation directed by Hwang Dong-hyuk, prompted the South Korean National Assembly to pass the "Togani Laws" to provide greater legal protections for children and vulnerable adults under state care and harsher penalties for those convicted of their abuse. At a time when Korean popular culture drives cultural production worldwide, Togani reminds us of the power of fiction to effect meaningful societal change. A story of courage in the face of corruption, Togani offers nuanced portraits of a failed young businessman seeking a new life as a teacher and his counterpart, a young woman committed to a career in human rights; a police officer of humble origins who rose through the ranks as he turns a blind eye to the abuse of students by the school's administrators; and a hearing-impaired teenage girl, a victim of that abuse, who cares deeply for the other children at the school. The book testifies to the legacy of neo-Confucian class conflict, gender disparity, and the vulnerability of those near the bottom of the social ladder. It is a heart-wrenching and provocative work that helped bring about change to a system it dared to challenge"--